An assessment of forest biomass carbon storage and ecological compensation based on surface area: A case study of Hubei Province, China. (July 2018) - He, Qingsong; Zeng, Chen; Xie, Peng; Liu, Yaolin; Zhang, Mengke
Abstract: Area is a basic indicator used in ecological investigations; conventional ellipsoid area describes the earth as a standard ellipsoid without considering undulation of the surface. However, using conventional ellipsoid area in ecological investigations introduces errors in the estimation of forest biomass carbon storage (BCS) in mountainous and hilly areas. In this study, BCS and ecological compensation of the 103 counties in Hubei Province, China, were measured using surface area. Results show that: (1) the surface area of Hubei Province is about 1.97 × 10 5 km 2, approximately 1.34 × 10 4  km 2 greater than the calculated ellipsoid area. In terms of forest area, the surface and ellipsoid areas are 6.52 × 10 4 and 5.92 × 10 4 km 2, respectively; forest area calculated using surface area is 10.13% greater than that using ellipsoid area. (2) There is a significant difference between the BCS measured in the two areas for mountain landforms, the average difference being 9.13 × 10 4  t. Plain landforms and hilly landforms have lower average differences, 2.63 × 10 3  t and 2.95 × 10 4  t, respectively. (3) The ecological compensation for forest ecosystems in Hubei Province is 33.47 billion Yuan and counties that should be assigned the highest ecological compensation are mainly located in western Hubei. (4) The differences in BCS calculated by the two area methods indicate a typical state of agglomeration in the region, where the western mountainous area belongs to the High–High cluster and the central–southern plain region to the Low–Low cluster. Findings from our investigation show an applied prospective for quantitatively estimating BCS and other resources in a much larger scale. Furthermore, ecological compensation transfer provides a reference for government decision makers to balance the interests of different regions for sustainable development and eco-environmental protection.